2022
DOI: 10.1021/acs.jpclett.1c04154
|View full text |Cite
|
Sign up to set email alerts
|

Midwavelength Infrared Colloidal Nanowire Laser

Abstract: Realizing bright colloidal infrared emitters in the midwavelength infrared (or mid-IR), which can be used for low-power IR light-emitting diodes (LEDs), sensors, and deep-tissue imaging, has been a challenge for the last few decades. Here, we present colloidal tellurium nanowires with strong emission intensity at room temperature and even lasing at 3.6 μm (ω) under cryotemperature. Furthermore, the second-harmonic field at 1.8 μm (2ω) and the third-harmonic field at 1.2 μm (3ω) are successfully generated thank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…They found that the time constant of the latter rising component depends on the power (excitation intensity) of the pump beam. They suggested that the τ 1 and τ 2 components originate from the accumulation of population in the conduction band and the stimulated emission, respectively . Similarly, the ultrafast τ 1 (∼1 ps) component in our experimental data (Figure a) could be assigned to the rapid increase or accumulation of the electronic population in the conduction band.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…They found that the time constant of the latter rising component depends on the power (excitation intensity) of the pump beam. They suggested that the τ 1 and τ 2 components originate from the accumulation of population in the conduction band and the stimulated emission, respectively . Similarly, the ultrafast τ 1 (∼1 ps) component in our experimental data (Figure a) could be assigned to the rapid increase or accumulation of the electronic population in the conduction band.…”
Section: Resultssupporting
confidence: 62%
“…Previous studies on the charge carrier dynamics of Te have been carried out with steady-state spectroscopy, transient photoconductivity, transient reflectivity, and transient microwave conductivity at various temperatures. Recently, several studies of electronic relaxation dynamics of Te at room temperature have been reported. , After photoexcitation, charge carriers (electrons and holes) are generated in the conduction and valence bands, respectively, and subsequently recombine to return to the initial ground state through different relaxation channels, such as direct recombination of the free and bound exciton, recombination of trapped electron and hole, and electronic relaxation to midgap trap state or defect states . As described in ref , the radiative recombination of charges in Te crystals is the dominant process (98%) at room temperature, with the remaining charges either undergoing the Shockley–Read–Hall recombination or transitioning to deeply trapped states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 54–56 ] The formation of built‐in electric field by the transfer of charges from the semiconductor to the electrolyte interface creates a space‐charge layer, which efficiently separates the charge carriers. [ 57 ] The amount of charge transferred influences the electric field potential and the width of the space‐charge layer ( W ), which can be quantitatively measured using Equation (11). W=2ε0εeNnormald(VFBkTe)…”
Section: Resultsmentioning
confidence: 99%
“…The decreased space‐charge‐width ( W ) further implies that the Ag 3 PO 4 contributes towards charge separation while RGO assists in charge transportation, of surface carriers, together enhancing light absorption. [ 57 ] Taking the condition of minimum recombination in the space‐charge layer, the absorption coefficient ( α ) can be estimated by Equation (12)1α=W, at λ= 450 nm…”
Section: Resultsmentioning
confidence: 99%